The Effect Of The Probing-Prompting Learning Model On Students' Critical Thinking Skills State Senior High School 1 Kuala - Desy Fitria; Mira Chairani; Mauliana Wayudi (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to determine the effect of the Probing Prompting learning model on students' critical thinking skills in class XI at SMA Negeri 1 Kuala. A quantitative approach with a quasi-experimental design using a nonequivalent control group design was employed. The study involved two classes: the experimental class, which received treatment using the Probing Prompting model, and the control class, which was taught using conventional methods. Research instruments included pre-tests and post-tests that had been tested for validity and reliability. Data analysis involved normality tests, homogeneity tests, and independent t-tests. The results showed a significant difference in post-test scores between the experimental and control classes. The average post-test score of the experimental class (77.21) was higher than that of the control class. Therefore, it can be concluded that the implementation of the Probing Prompting learning model has a significant effect on improving students' critical thinking skills in economics subjects.